Метаболические и аутоиммунные корреляты структурных изменений головного мозга больных с рассеянным склерозом = Metabolic and autoimmune correlates of brain's structural changes in disseminated sclerosis patients - Anatoliy I. Gozhenko; Olga Uy. Naumenko (Kazimierz Wielki University, 2015)
Gozhenko A I, Naumenko O Y. Метаболические и аутоиммунные корреляты структурных изменений головного мозга больных с рассеянным склерозом = Metabolic and autoimmune correlates of brain's structural changes in disseminated sclerosis patients. Journal of Education, Health and Sport. 2015;5(1):163-170. ISSN 2391-8306. DOI: 10.5281/zenodo.14792 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A163-170 https://pbn.nauka.gov.pl/works/533080 http://dx.doi.org/10.5281/zenodo.14792 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.     Метаболические и аутоиммунные корреляты структурных изменений головного мозга больных с рассеянным склерозом   METABOLIC AND AUTOIMMUNE CORRELATES OF BRAIN'S STRUCTURAL CHANGES IN DISSEMINATED SCLEROSIS PATIENTS   А.И. Гоженко, О.Ю. Науменко AI Gozhenko, OY Naumenko   Украинский НИИ медицины транспорта, г.Одесса, Украина Ukrainian Research Institute of Medical Transport, Odessa, Ukraine badiuk_ns@ukr.net   Резюме Авторы на основании данных комплексного обследования 64 больных, у которых, на основании клинико-неврологического исследования, диагностирован рассеянный склероз, изучали связь между структурными изменениями головного мозга и состоянием цикла мочевой кислоты и интенсивностью аутоиммунного процесса. Выявлено, что структурные изменения головного мозга не связаны с половозрастными особенностями больных, но всегда сопровождаются сниженным содержанием мочевой кислоты и наличием миелинассоциированного гликопротеида. Авторы указывают, что величина двух последних показателей коррелирует с длительностью процесса. Авторы полагают, что изменения в активности цикла мочевой кислоты способствуют возникновению аутоиммунного процесса, который обеспечивает структурное повреждение мозга. Нарастание биохимических и аутоиммунных нарушений в динамике заболевания, по мнению автора, способствуют сохранению повреждений мозга и нивелируют компенсаторные изменения в нем.   Ключевые слова: рассеянный склероз, мочевая кислота, структурные повреждения мозга.       Abstract Clinical-and-neurological examination of 64 patients proved the diagnosis of disseminated sclerosis (DS). The relation between brain's structural changes (BSC), uric acid cycle and autoimmune process intensity has been studied in the group under observation. It has been revealed that BSC have no connection with sexual and age peculiarities  of the patients and are always followed by the decreased content of uric acid and the presence of myelin-associated glycoprotein. The amount of the two latter in indexes correlates with the process time duration. The Authors suppose that  uric acid cycle changes promote the appearance of autoimmune process which in its turn confers BSC. Aggravation of biochemical and autoimmune disturbances in the dynamics of the disease leads to brain's disorders preservation and levels its compensatory changes.   Key words: disseminated sclerosis, uric acid, structural changes of brain.